Mind–Body Exercises for PTSD Symptoms, Depression, and Anxiety in Patients With PTSD: A Systematic Review and Meta-Analysis - Zhu, Lin; Li, Long; Li, Xiao-zhi; Wang, Lin (Frontiers in Psychology, 2022)
Objectives: The present study aimed to systematically analyze the effects of mind-body exercise on PTSD symptom, depression and anxiety among patients with post-traumatic stress disorder (PTSD) and to provide a scientific evidence-based exercise prescription. Methods: Both Chinese and English databases (PubMed, Web of Science, the Cochrane Library, EMBASE, VIP Database for Chinese Technical Periodicals, China National Knowledge Infrastructure, and Wanfang) were used as sources of data to search for randomized controlled trials (RCTs) published between January 1980 to November 2020 relating to the effects of mind-body exercise on on PTSD symptom, depression and anxiety in PTSD patients. Sixteen eligible RCTs were ultimately included in the meta-analysis. Results: Mind-body exercise had significant benefits on PTSD symptom(standard mean difference (SMD)= -0.41, 95% confidence interval (CI) −0.64 to −0.19, p < 0.001), depression (SMD= −0.35, 95% CI (−0.55 to −0.15), p < 0.001) , and anxiety (SMD= −0.31, 95% CI −0.74 to −0.12 , p < 0.001) among patients with PTSD. Subgroup analysis indicated that, for PTSD symptom, 60-150 min per session for 8-16 weeks of mindfulness had a greater effect on on patients with PTSD patients who younger than 45. For depression, 150-180 minutes of yoga exercises 1 time per week was more effective. For anxiety, due to the limited number of RCTs that were eligible, it is not possible to determine the optimal frequency, time, duration and type of mind-body exercise for people with PTSD. Conclusions: Mind-body exercise was found to lead to significant improvements in PTSD symptom, depression and anxiety in PTSD patients and can be used as an effective method for clinical exercise intervention in these patients. However, more objective, scientific, and effective RCTs are needed to confirm this conclusion.